Potential application of ginger, clove and thyme essential oils to improve soft cheese microbial safety and sensory characteristics. (August 2021) - Ahmed, Lamiaa Ibrahim; Ibrahim, Nehal; Abdel-Salam, Ayah Badawy; Fahim, Karima Mogahed
Abstract: Due to consumers growing concerns about synthetic preservatives, essential oils (EOs) come into the focus of pharmaceutical and food applications as natural alternatives because of their inherent antimicrobial activity. However, EOs food applications have been challenged by their strong aroma that adversely affects consumers acceptability. In this study, EOs of Zingiber officinale (ginger), Syzygium aromaticum (clove), and Thymus vulgaris (thyme) were extracted and assessed for their potential use to produce cheese with high degree of microbial safety and sensory acceptability. Phytochemical profiling showed camphene and zingiberene as major constituents in ginger oil, whereas thymol and eugenol represented the chief volatiles in thyme and clove, respectively. The EOs antimicrobial activity against seven strains of pathogenic and spoilage bacteria, yeast and mold revealed MIC of 0.001%. Additionally, studied EOs demonstrated interesting safety profile displaying good to very weak cytotoxicity on human hepatocellular carcinoma (HepG2) with CC50 6.31–452.95 μg/mL and very low cytotoxicity on normal human lung fibroblasts (WI-38) with CC50 728.94–841.66 μg/mL. Sensory characterization of EOs-fortified laboratory manufactured fresh soft cheese displayed scores significantly higher than control samples ( P  < 0.001) in relation to overall acceptability. Viability study of Methicillin-resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa in fortified cheese matrix showed complete reduction of S. aureus at the end of first and second weeks of storage of thyme and ginger fortified cheese, respectively, and about 50% reduction of P. aeruginosa by the end of storage period. This study opens interesting new perspectives for the agro-industrial applications of EOs as natural preservatives. Highlights: GC-MS revealed camphene, thymol & eugenol as major volatiles of ginger, thyme & clove essential oils. Remarkable antimicrobial activity against seven bacterial & fungal strains (MIC of 0.001%). Complete inhibition of S. aureus in inoculated fortified fresh soft cheese matrix. Improvement of cheese overall acceptability along with good safety profile. Ginger and thyme essential oils are potential natural preservatives in fresh soft cheese.